Two Cultural Models on Infant Motor Development: Middle Class Parents in Israel and the Netherlands - Oudgenoeg-Paz, Ora; Atun-Einy, Osnat; van Schaik, Saskia D. M. (Frontiers in Psychology, 2020)
Culture influences the way parents shape children’s environment. Two studies examined cross-cultural differences in parental practices related to motor development in Israel and the Netherlands. In the first study, 198 Dutch and 206 Israeli parents of infants aged 1-7.5 months completed questionnaires measuring parental practices and beliefs regarding motor development. In the second study, 30 Dutch and 30 Israeli parents completed the same questionnaires when their children were 2 and 10 months old. While similarities were found across the cultures, Israeli parents practiced infant prone positioning more. Additionally, Dutch infants spent substantial more time in the playpen. Furthermore, beliefs stressing stimulation and stimulating practices (both more frequent within Israeli parents) predicted better prone skills, shown by the Israeli infants. Findings highlight the diversity of parental practices related to infant motor development.